Risk Factors for the Incidence and Severity of Acute Kidney Injury After Liver Transplantation - Zhang, Dali; Liu, Zhenwen; Bi, Jing feng; Liu, Hongling; Gao, Yinjie (Turkish Journal of Gastroenterology, 2021)
Background/Aims: To explore risk factors of acute kidney injury (AKI) and its severity after liver transplantation. Materials and Methods: This was a retrospective cohort of consecutive adults undergoing orthotopic liver transplantation (OLT) at a referral hospital. Risk factors for AKI from 1week post-liver transplantation and 4-week outcomes were analysed. Further analyses of factors that influenced the severity of AKI were also performed. Results: A total of 204 patients were included. AKI was found in 55.4% of patients in the first week after OLT. Risk factors for AKI were recipient’s sex, BMI, preoperative creatinine, preoperative hepatic encephalopathy, cold ischaemia time, duration of surgery, duration of inferior vena clamping, postoperative peak lactate and postoperative peak AST, which were higher in the AKI group. Four weeks after liver transplantation, 20.4% of AKI patients still had abnormal renal function and a mortality rate of 3.6%, and these values were significantly higher than those of patients without AKI (P<0.05). Conclusion: Preoperative, intraoperative and postoperative factors can all lead to AKI after OLT.